ANALISIS KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS III DI SDN WATESHAJI 01 KABUPATEN PATI - Dwi Rahmawati, Wadina; Fita Asri Untari, Mei; Wijayanti, Arfilia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Based on the results of daily formative assessments in the Indonesian Language subject and interviews with the third-grade teacher at SDN Wateshaji 01, Pati Regency, students’ reading comprehension skills had not yet reached an optimal level. This assessments showed that out of 13 students, 5 students (38.46%) had achieved the Minimum Mastery Criterion (KKM), while 8 students (61.54%) had not achived the Minimum Mastery Criterion (KKM). In addition, interview revealed that some students were still not fluent in reading, continued to spell out words, experienced difficulties in understanding texts, and showed low interest in reading. This study aimed to describe the reading comprehension skills of third-grade students at SDN Wateshaji 01, Pati Regency. This research employed a descriptive qualitative approach. Data were collected through tests, interviews, and documentation. The reading comprehension indicators included: (1) answering questions about facts and details using 5W+1H, (2) identifying the main idea, (3) drawing conclusions, (4) identifying moral messages, and (5) providing responses to reading texts. Data validity was ensured through technique and source triangulation, while data were analyzed using the Miles and Huberman model. The results involving 13 students showed that their reading comprehension skills were categorized as fair, with an average score of 68.9. Five students (38.5%) were categorized as good, six students (46.2%) as fair, and two students (15.4%) as poor. Students were able to understand explicit information but still experienced difficulties in identifying the main idea and drawing conclusions. Therefore, teachers need to strengthen reading habits and provide regular reading comprehension practice to improve students’ comprehension skills.